Services Management System of Library Educational Institution(Study at the Archives and Library Office, Kendal) - Muhammad Fauzi (Jurnal Ekonomika dan Bisnis, 2021)
This study aims to determine the challenges faced in increasing public interest in reading, knowing the service management of visitors, knowing mobile library services that meet the information needs of visitors and knowing how far the level of success of customer service management To achieve the intended objectives, this research uses descriptive analysis method, this type of qualitative research with descriptive analysis method. With the method of data collection, observation, interviews, and documentation. In this study, the informants were the Head of the Service Section, Service Staff, and visitors. The results of this study indicate that the service management of library users at the Department of Archives and Libraries of Kendal Regency is the same as the service standards in other libraries, the service system applied is to serve users, fill in guest books, and choose the library materials needed. The success of Library Service Management at the Department of Archives and Libraries of Kendal Regency has not been maximized due to the fluctuation of visiting visitors because the need for libraries is not much fulfilled such as facilities and infrastructure owned are still insufficient, information resources in the form of collections of library materials are still limited, incomplete books collections for visitors.